2002
DOI: 10.1002/ffj.1057
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the essential oils from three Laggera Spp. from Cameroon

Abstract: The essential oils from the leaves of Laggera alata var. montana C. D. Adams, and Laggera gracilis (O. Hoffm. & Muschl.) C. D. Adams, and those from leaves, roots and stems of Laggera oloptera (DC.) C. D. Adams from the western highlands of Cameroon were analysed by GC and GC-MS. The essential oils of L. alata var. montana and L. gracilis were found to be rich in dimethoxy-p-cymene (34% and 33%, respectively). The other most abundant components in these oils were 7-epi--eudesmol (21%), juniper camphor (7%) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The essential oil of L. alata grown in Nigeria 12 and Cameroon; 14 L. aurita grown in India; 18 L. gracilis grown in Cameroon; 14 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oil of L. alata grown in Nigeria 12 and Cameroon; 14 L. aurita grown in India; 18 L. gracilis grown in Cameroon; 14 …”
Section: Resultsmentioning
confidence: 99%
“…5,6 Many phytochemical investigations have been performed on the non-volatile and volatile constituents of different species of Laggera from various countries. [7][8][9][10][11][12][13][14][15][16][17] In India, L. aurita has also been studied on a few occasions. [18][19][20] However, a literature survey revealed that there are no reports available on the phytochemical aspects of L. crispata from India.…”
Section: Introductionmentioning
confidence: 99%
“…difference in activity observed between the essential oil could be due to their chemical dissimilarities both quantitatively and qualitatively. Indeed, the essential oil of L. alata var montana is mainly constituted of dimethoxy-p-cyrnene (34%) and epi-y-endesmol (2 1.4%) [7]. Those of leaves and flowers of E. floribundus are rich in limonene (9.5 % for leaves and 3.7 % for the flowers) and i n polyacetylated compounds 1 ike (E)-2-lachnophyllum ester (23.7 % for leaves and 3.4 % for the flowers) [8].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the essential oil of L. alata var montana is mainly constituted of dimethoxy-p-cyrnene (34%) and epi-y-endesmol (2 1.4%) [7]. Those of leaves and flowers of E. floribundus are rich in limonene (9.5 % for leaves and 3.7 % for the flowers) and i n polyacetylated compounds 1 ike (E)-2-lachnophyllum ester (23.7 % for leaves and 3.4 % for the flowers) [8]. The observed activities could be attributed to these major components while recognizing that this activity is often the result of the combined action (antagonism, synergy and potentiation) of all the constituents of an essential oil talung into consideration even.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation